Türk Ceza Kanunu'nda nefret ve ayırımcılık suçu (m.122) - Demet, Zehra (My University, 2024)
Çalışmamızın konusu olan Nefret ve Ayrımcılık Suçu 5237 Sayılı Türk Ceza Kanunu’nun 122. maddesinde “ Dil, ırk, milliyet, renk, cinsiyet, engellilik, siyasi düşünce, felsefi inanç, din veya mezhep farklılığından kaynaklanan nefret nedeniyle; 1) Bir kişiye kamuya arz edilmiş olan bir taşınır veya taşınmaz malın satılmasını, devrini veya kiraya verilmesini 2) Bir kişinin kamuya arz edilmiş belli bir hizmetten yararlanmasını, 3) Bir kişinin işe alınmasını, 4) Bir kişinin olağan bir ekonomik etkinlikte bulunmasını engelleyen kimse bir yıldan üç yıla kadar hapis cezası ile cezalandırılır.” şeklinde düzenlenmiştir. Madde metninde belirtilen seçimlik hareketlerden birinin gerçekleştirilmesi ile suç tamamlanmaktadır. Ayrımcılık yasağı ulusal ve uluslararası hukuki metinlerde kapsamlı olarak düzenlenmektedir Kanun koyucu anayasal bir ilke olan eşitlik ilkesinin bir uzantısı olan ayrımcılık yasağının önemine binaen cezai yaptırım belirlemiştir. Madde metninin ilk halinde nefret kavramı bulunmazken; 2014 yılında gerçekleştirilen değişiklikle nefret saiki madde metnine eklenmiştir. Kanunda her ne kadar nefret ve ayrımcılık suçu olarak düzenlenmişse de suçun bir nefret suçu olup olmadığı ayrıca değerlendirilecektir. Ayrımcılık ilk olarak 1948 tarihli Birleşmiş Milletler Evrensel İnsan Hakları Bildirgesinde yasaklanmış olmakla birlikte birçok uluslararası sözleşmeye de konu edilmiştir. Ayrımcılık kavramı en yalın haliyle bir kişi ya da bir grubun sahip olduğu birtakım özelliklerden ötürü, hak ve özgürlüklerden yararlanmada, haklı bir gerekçe olmaksızın, başka kişi ya da gruplara karşı daha aleyhte muamele görmesi olarak tanımlanabilir. Çalışmamızda suç tipi detaylıca incelenirken, ulusal ve uluslararası hukuki metinlerden, ulusal ve uluslararası mahkeme kararlarından yararlanılacaktır. İlgili suç tipi ile korunan hukuki değer ve suçun maddi unsurları, manevi unsuru ve suçun nitelikli halleri ve suçun özel görünüş biçimleri detaylıca incelenecektir. Günümüzde insanların hizmetine sunulan ve birçok alanda kullanılan yapay zekalı varlıkların cezai ve hukuki sorumlulukları doktrinde tartışılmaktadır. Yapay zekalı varlıklar çalışmamızda incelenecek nefret ve ayrımcılık suçunun maddi unsurlarını yerine getirebildiği alanlarda kullanılabilmektedir. Bu nedenle çalışmamızda teknolojik gelişmeler nedeniyle hayatımızın birçok alanında kullanılan yapay zekalı varlıkların nefret ve ayrımcılık suçu bakımından cezai sorumlulukları, kusur yetenekleri ayrıca incelenecektir.

Hate and Discrimination Crime, which is the subject of this study, is defined in Article 122 of the Turkish Criminal Code No. 5237. Article 122 of the Turkish Criminal Code No. 5237 is regulated as follows: (1) Any person who (a) Prevents the sale, transfer or rental of a movable or immovable property offered to the public, (b) Prevents a person from enjoying services offered to the public, (c) Prevents a person from being recruited for a job, (d) Prevents a person from undertaking an ordinary economic activity on the ground of hatred based on differences of language, race, nationality, color, gender, disability, political view, philosophical belief, religion or sect shall be sentenced to a penalty of imprisonment for a term of one year to three years. The offense is completed with the realization of one of the optional acts specified in the text of the article. The prohibition of discrimination is extensively regulated in both national and international legal texts as well as legislative basis’. The legislator has determined criminal sanctions due to the importance of the prohibition of discrimination, that is an extension of the principle of equality, which is a constitutional one. While the concept or comprehension of hate was not included in the first version of the article, hate motivation was added to the text of the article with the amendment made in 2014. Although it is regulated as a crime of hate and discrimination in the law, whether the crime is a hate crime will be evaluated individually. Furthermore, discrimination was first prohibited by the United Nations Universal Declaration of Human Rights of 1948 and has been the subject of many international conventions. In its simplest form, the concept of discrimination can be defined as the treatment towards an individual or a group more unfavorably than other individuals or groups by the contexture of rights and freedoms, without justification, due to certain characteristics that a person or a group has. In this study, while analyzing the crime type in detail, national and international legal texts, national and international court decisions will be utilized. The legal value protected by the relevant crime type and the material elements of the crime, the moral element and the qualified forms of the crime and the special forms of the crime will be examined in detail. Contemporarily, the criminal and legal responsibilities of artificial intelligent beings, which are offered to the service of people and used in many fields, are discussed in the doctrine. Artificially intelligent beings can be used in areas where they can fulfill the material elements of the crime of hate and discrimination, which will be examined in our study. Hereby, in this context, the criminal responsibilities and fault abilities of artificial intelligent beings, which are used in many areas of human life due to technological developments, will be examined separately in terms of the crime of hate and discrimination.
Keywords: artifical intelligence; ayırımcılık yasağı; Ayrımcılık; Criminal liability of artifical intelligence; Discrimination; Eşitlik; Hate crimes; hatred and discrimination crime within the Turkish Penal Code article 122; Law and legislation; Nefret suçları; non- discrimination; Turkey; Türk Ceza Kanunu’nda Nefret ve ayırımcılık suçu Equality; Türkiye; yapay zeka; yapay zekanın cezai sorumluluğu; Yasa ve yasama